2021
DOI: 10.3389/fpls.2021.713890
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping and Validation for Kernel Area and Circumference in Common Wheat via High-Density SNP-Based Genotyping

Abstract: As an important component, 1,000 kernel weight (TKW) plays a significant role in the formation of yield traits of wheat. Kernel size is significantly positively correlated to TKW. Although numerous loci for kernel size in wheat have been reported, our knowledge on loci for kernel area (KA) and kernel circumference (KC) remains limited. In the present study, a recombinant inbred lines (RIL) population containing 371 lines genotyped using the Wheat55K SNP array was used to map quantitative trait loci (QTLs) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The employment of LD blocks as markers can notably decrease the possibility of false positives during multiple hypotheses in the GWAS model [ 40 ]. In this study, all 16 additive QTL were identified using three genetic map-based models ( Table 3 ), demonstrating their detection power in QTL mapping [ 44 , 45 , 46 ], whereas six of them were validated by RTM-GWAS. These results indicate that the value of using multiple models that combine the genetic map-based and GWAS models facilitates the detection of QTL with small effects and the validation of QTL.…”
Section: Discussionmentioning
confidence: 77%
“…The employment of LD blocks as markers can notably decrease the possibility of false positives during multiple hypotheses in the GWAS model [ 40 ]. In this study, all 16 additive QTL were identified using three genetic map-based models ( Table 3 ), demonstrating their detection power in QTL mapping [ 44 , 45 , 46 ], whereas six of them were validated by RTM-GWAS. These results indicate that the value of using multiple models that combine the genetic map-based and GWAS models facilitates the detection of QTL with small effects and the validation of QTL.…”
Section: Discussionmentioning
confidence: 77%
“…Then, the KNPS, TKW, GL, GW, and GDR were measured by an SC-G automatic seed analysis and 1000-grain weight analyzer (Wanshen, Hangzhou, China). These data were recruited from our previous studies [ 43 , 44 ]. The GY was calculated by the formula = SN × KNPS × (TKW/1000).…”
Section: Methodsmentioning
confidence: 99%
“…Common wheat (Triticum aestivum L.) is one of the most important crops in the world and provides approximately 20% of the food in the human diet [1]. It is very important to maintain and continue increasing the yield of common wheat to relieve the pressure exerted by the decrease in farmland and the increase in the population [2]. However, stripe rust and powdery mildew, caused by Puccinia striiformis Westend.…”
Section: Introductionmentioning
confidence: 99%